Deconvolution of Mono-Energetic and Multi-Lines Gamma-Ray Spectra Obtained with NaI(Tl) Scintillation Detectors Using Direct Matrix Inversion Method - Kumwenda, Mwingereza J. (Tanzania Journal of Engineering and Technology, 2021)
Performance of a NaI(Tl) scintillation detector based on the gamma-ray spectroscopy system is not satisfactory in retaining its original peak (which is delta like function) of various gamma ray spectrum. The method of achieving precise peak for the various gamma ray was conducted by converting the observed pulse-height distribution of the NaI(Tl) detector to a true photon spectrum. This method is obtained experimentally with the help of an inverse matrix deconvolution method. The method is based on response matrix generated by the Monte Carlo simulation based on Geant4 package of mono-energy gamma-ray photon ranging from 0.050 to 2.04 MeV in the interval of 10 keV. The comparison of the measured and simulated response function was also performed in order to authenticate the simulation response function. Good agreement was observed around the photo-peak region of the spectrum, but slight deviation was observed at low energy region especially below 0.2 MeV. The Compton backscattering and Compton continuum counts was significantly transferred into the corresponding photo-peak and consequently the peak to total(P/T) ratio was improved. The P/T ratio results obtained after application of the deconvolution method taken with three calibration sources with gamma-ray ' s energies of 81 keV, 303 keV and 356 keV (for 133Ba), 662 keV (for 137Cs), 1173 keV and 1333keV (for 60Co), were improved from(to) 0.50(0.90), 0.40(0.83), 0.57(0.93), 0.31(0.92), 0.18(0.84) and 0.15(0.83), respectively. Keywords: NaI(TI) detectors, Deconvolution/Unfolding, Response function, Gamma- ray spectrum, Geant4 simulation